A new structure family of oxide-ion conductors based on BaGdInO4. Issue 17 (22nd April 2020) - Yaguchi, Hiroshi; Fujii, Kotaro; Yashima, Masatomo
Abstract : We prepared new materials BaGdInO4 and BaGd0.9 A 0.1 InO3.95 ( A = Mg, Ca, Sr) for the first time. These oxides belong to a new structure family of one-dimensional oxide-ion conductors and exhibit conductivities comparable to BaNdInO4 -based oxides. Abstract : Ba R InO4 -based materials ( R = Nd, Sm, Ho, Y, Er, and Yb) have attracted much attention due to their oxide-ion conduction and unique (110) layered perovskite structures (monoclinic P 21 / c BaNdInO4 -type structure). Here, we report new compounds BaGdInO4 (GdBaInO4 ) and BaGd0.9 A 0.1 InO3.95 ( A = Mg, Ca, and Sr). It was found that these compounds belong to a new structure family of oxide-ion conductors. Surprisingly, the single-crystal and powder X-ray diffraction analyses have shown that the crystal structures of BaGdInO4 and BaGd0.9 A 0.1 InO3.95 ( A = Mg, Ca, and Sr) are quite different from those of the monoclinic Ba R InO4 -based materials. We found that BaGdInO4 and BaGd0.9 A 0.1 InO3.95 ( A = Mg, Ca, and Sr) have an orthorhombic Pnma Ba2 Y2 CuPtO8 -type structure consisting of InO5 square pyramids, InO6 octahedra, (Gd, A )O7 polyhedra (monocapped trigonal prisms) and Ba cations where (Gd, A ) denotes Gd or Gd0.9 A 0.1 . Four edge-sharing (Gd, A )O7 polyhedra build an infinite one-dimensional ((Gd, A )4 O20 )∞ chain. Oxide-ion conduction was confirmed for BaGdInO4 and BaGd0.9 Ca0.1 InO3.95 by the electrical conductivity measurements at different oxygen partial pressures P (O2 ). The oxide-ion conductivity of BaGd0.9 Ca0.1 InO3.95 was 381 times higher than that of BaGdInO4 at 400 °C, which was attributed to the higher oxygen vacancy concentration in BaGd0.9 Ca0.1 InO3.95 . The oxide-ion conductivity of BaGd0.9 Ca0.1 InO3.95 was comparable to those of monoclinic BaNdInO4 -type Ba R InO4 -based materials. The bulk conductivity of BaGd0.9 Ca0.1 InO3.95 was 1.3 × 10 −3 S cm −1 at 700 °C and P (O2 ) = 10 −4 atm in the electrolyte domain. The bond valence-based energy landscapes of BaGd0.9 Ca0.1 InO3.95 and BaGdInO4 indicated one-dimensional oxide-ion migration pathways on the faces of (Gd, Ca)O7 polyhedra along the ((Gd, Ca)4 O20 )∞ chain in the b direction. The discovery and unique features of the orthorhombic BaGdInO4 -based materials might develop the materials chemistry of oxide-ion conductors.